Non-noble metal (Ni, Cu)-carbon composite derived from porous organic polymers for high-performance seawater electrolysis. (15th November 2021) - Gopi, Sivalingam; Vadivel, Selvamani; Pinto, Leandro M.C.; Syed, Asad; Kathiresan, Murugavel; Yun, Kyusik
Abstract: The hydrothermal preparation of o -dianisidine and triazine interlinked porous organic polymer and its successive derivatisation via metal infusion (Ni, Cu) under hydrothermal and calcination conditions (700 °C) to yield pristine (ANIPOP-700) and Ni/Cu decorated porous carbon are described here (Ni-ANIPOP-700 and Cu-ANIPOP-700). To confirm their chemical and morphological properties, the as-prepared materials were methodically analyzed using solid state 13 C and 15 N NMR, X-ray diffraction, Raman spectroscopy, field emission scanning and high resolution transmission electron microscopic techniques, and x-ray photoelectron spectroscopy. Furthermore, the electrocatalytic activities of these electrocatalysts were thoroughly investigated under standard oxygen evolution (OER) and hydrogen evolution reaction (HER) conditions. The results show that all of the materials demonstrated significant activity in water splitting as well as displayed excellent stability (22 h) in both acidic (HER) and basic conditions (OER). Among the electrocatalysts reported in this study, Ni-ANIPOP-700 exhibited a lower overpotential η10 of 300 mV in basic medium (OER) and 150 mV in acidic medium (HER), as well as a lower Tafel slope of 69 mV/dec (OER) and 181 mV/dec (HER), indicating 30% lower energy requirement for overall water splitting. Gas chromatography was used to examine the electrolyzed products. Graphical abstract: Image 1 Highlights: Cu, Ni incorporated POP based on o -anisidine-triazine linkages were prepared. Ni-ANIPOP-700 exhibited better OER activity under both acidic and basic conditions. Ni-ANIPOP-700 showed overpotential η10 of 300 mV for OER and 150 mV for HER. Ni-ANIPOP700 produced 0.0044 mol H2 at cathodic half-cell. Ni-ANIPOP-700 catalyst exhibited excellent catalytic activity and stability (22 h).